The Poaceae-associated genus Bamboosiella (Thysanoptera, Phlaeothripidae) from India with one new species - Kumar, Vikas; Tyagi, Kaomud (Zootaxa, 2014)
Bamboosiella venkataramani sp. n. is described from India based on specimens collected on grass clumps from the Karnataka State of India. A key is provided for identification of seven Indian species of the genus Bamboosiella.